2017
DOI: 10.1186/s13104-017-2539-3
|View full text |Cite
|
Sign up to set email alerts
|

Latrine coverage and its utilisation in a rural village of Eastern Nepal: a community-based cross-sectional study

Abstract: BackgroundA little more than 1/3rd of the rural households in Nepal have improved latrine facility. The government of Nepal is working towards making an open defecation free area all over Nepal. There is no data found in literature searches regarding the status of latrines and its utilisation in Nepal. This study aims to estimate the coverage and utilisation of latrine and its associated factors in a rural community of Nepal.MethodsWe conducted a cross sectional study in March 2015–September 2015 among 625 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
35
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 17 publications
16
35
3
1
Order By: Relevance
“…Families not having under 5 year child, utilize toilet significantly more than those family having under 5 children in their family, such type of similar finding were also find out in study conducted by Biran et al and study conducted by Yimam et al 7,12 Regarding the association of family size with toilet utilization, this family size was not found associated with toilet utilization in present study and similar finding is also seen in study conducted by Budhathoki et al and study conducted by Koyra et al 8,14…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Families not having under 5 year child, utilize toilet significantly more than those family having under 5 children in their family, such type of similar finding were also find out in study conducted by Biran et al and study conducted by Yimam et al 7,12 Regarding the association of family size with toilet utilization, this family size was not found associated with toilet utilization in present study and similar finding is also seen in study conducted by Budhathoki et al and study conducted by Koyra et al 8,14…”
Section: Discussionsupporting
confidence: 89%
“…12 Toilet utilization is more among younger age group peoples which is also seen in study done by Biran et al as this might be because of younger peoples aware about proper utilization and ready to change behaviour which is quite difficult in old age person. 12 In present study literate participant and literate family head utilized toilet more significantly as compare to illiterate participant and similar findings were seen in study conducted by Yimam et al, Debesay et al and Koyra et al while this association of education with toilet utilization was not found in study conducted by Budhathoki et al 7,8,13,14 Toilet utilization was significantly higher among the urban population as compare to rural population. This difference in toilet utilization may be because of higher socio-economic status and higher educational status of urban population.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A study in India found that the practice of keeping livestock near the water storage can reduce the positive health impact of other sanitation interventions, such as a reduction in open defecation practices [28]. Achieving open defecation free (ODF) status has been one of the main focuses of Nepal's national government since the 2000s [29]. The situation is yet more complex in Nepal, where traditional and dominant religious culture greatly honors livestock ownership [30].…”
Section: Factors Related To Water Qualitymentioning
confidence: 99%
“…Studies show that the unavailability of water facilities at toilets motivates people for open defecation and disuse of toilets [20]. Similarly, use of unprotected water for drinking is considered a major factor for diarrheal disease (21). Furthermore, mass media like television, radio, print media, internet, etc.…”
Section: Discussionmentioning
confidence: 99%